Teaching The Concept of Line Relationships Using The Inquiry Method in Fourth-Grade MI/Elementary Schools - Sufyan, Qurrotul A’yun; HS, Dedi Eko Riyadi; Maftuhah, Maftuhah; Mushollin, Ahmad (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
This study aims to find out how the material for the relationship between lines is learned using the application of the inquiry method, as we all know that the term inquiry is used on various occasions, especially in the learning process. This study used the linra method. The inquiry method is one of the methods that can be applied to learning mathematics in elementary schools. Inquiry places more emphasis on search. Inquiry requires students to become researchers or scientists, but in the context of learning, students are still guided by the teacher, therefore inquiry is said to be a guided discovery method. Inquiry can be carried out through several systematic steps, namely: 1) Formulating the problem; 2) Proposing a hypothesis; 3) Collecting data; 4) Test the hypothesis based on the data collected; and 5) Make conclusions. This paper will describe the application of the inquiry method in the matter of interlinear relationships in Class IV MI/SD